Implementasi Trunk Interkoneksi Multi Server menggunakan Singleboard Komputer - Alwalid Nouvatie; Martono Dwi Atmadja; Waluyo Waluyo (Politeknik Negeri Malang, 2021)
Voice over Internet Protocol (also called VoIP, IP Telephony, Internet Telephony or Digital Phone)is a technology that enables remote voice conversation through internet media. Voice data is converted into digital code and streamed over a network that delivers data packets, rather than through a regular analog telephone circuit. In VoIP communication,users make telephone connection through a terminal in the form of a PC or a regularphone. By calling voip, manyadvantages that can be taken in terms of costare obviously cheaper than traditional phone rates, because IP networks are global. IP Phone can be added, moved and changed. This is because VoIP can be installed in any ethernet and IP address,unlike conventional phones that must have their own port in Sentral or PBX (Private branch exchange). In this study implementing connectedness between servers using single board computer installed elastix operating system that aims to implement prefix for between servers and use some audio codecs. The results of telephone research using prefix and without prefix as many as 6 clients or 3 pasng calls simultaneously the highest packet loss value in codec speex with prefix of 2.34%. The highest bandwidth value used is with pcmu prefix codec with an average of 82.3 Kbps and without prefix 79.3 Kbps. Keyword : Server, VoIP, IP Telphony, Internet telephony, Digital Phone, IP Address, PBX, Codec, Prefix.